Analysis of Physician Leadership and Leadership Development in Government-Owned Healthcare Institutions: A Mixed-Method Study - Arifatul Khorida; Kartini Hasballah; Andreasta Meliala; Nurjannah Nurjannah (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Physician involvement in leadership roles within healthcare institutions has been declining worldwide, despite evidence linking physician leadership with improved healthcare outcomes. Objective: To examine physicians’ leadership roles, individual characteristics, and factors influencing their leadership effectiveness in government-owned healthcare institutions in Indonesia, and to propose a contextually appropriate leadership development model. Methods: A mixed-method design was used. Phase I was a qualitative study conducted through in-depth interviews and focus group discussions with 49 physicians from 31 institutions, analyzed using thematic framework analysis (NVivo 12, COREQ guidelines). Phase II was a quantitative survey involving 358 physicians from 25 institutions, analyzed using structural equation modeling with partial least squares (SEM-PLS). Results: Qualitative findings revealed structural, personal, and managerial barriers to leadership engagement, including time constraints, administrative burdens, inadequate incentives, and political influences. However, physicians were perceived as strategic leaders due to their technical expertise, tiered experiences, and credibility in clinical management. The quantitative model demonstrated strong reliability and validity. Individual differences (experience, efficacy) significantly influenced motivation to lead (β=0.577), leadership behavior (β=0.496), and leadership outcomes (β=0.176, p<0.001). Motivation (β=0.197) and behavior (β=0.604) also significantly predicted leadership outcomes. Conclusion: Despite low participation, physicians possess leadership characteristics that positively contribute to leadership effectiveness. Physician leadership development should be institutionally driven, integrating managerial competencies with technical expertise, while addressing structural and motivational barriers.